1993
DOI: 10.1161/01.atv.13.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol, a novel cyclic AMP phosphodiesterase inhibitor, prevents reocclusion after coronary arterial thrombolysis with recombinant tissue-type plasminogen activator.

Abstract: Inhibitors of cyclic nucleotide phosphodiesterase hydrolysis of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate are known to inhibit platelet aggregation, which plays an important role in acute reocclusion after thrombolysis in acute myocardial infarction. In the present study of a canine preparation of coronary artery thrombosis superimposed on high-grade stenosis, we tested whether the antithrombotic agent cilostazol, an inhibitor of cAMP phosphodiesterase, could prevent acute reoccl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 38 publications
(13 reference statements)
0
8
0
2
Order By: Relevance
“…Studies in animals showed that CIL suppresses atherosclerosis formation in low-density lipoprotein receptor (Ldlr)-null mice by suppressing superoxide and TNF-α formation, and thereby reducing NF-κB activation/transcription, VCAM-1/MCP-1 expressions, and monocyte recruitments [65]. In the dog, CIL prevented coronary re-thrombosis following thrombolysis in a model of coronary artery thrombosis superimposed on high-grade stenosis [66].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals showed that CIL suppresses atherosclerosis formation in low-density lipoprotein receptor (Ldlr)-null mice by suppressing superoxide and TNF-α formation, and thereby reducing NF-κB activation/transcription, VCAM-1/MCP-1 expressions, and monocyte recruitments [65]. In the dog, CIL prevented coronary re-thrombosis following thrombolysis in a model of coronary artery thrombosis superimposed on high-grade stenosis [66].…”
Section: Discussionmentioning
confidence: 99%
“…In cats, cilostazol is not only an effective anti-platelet therapy, but is also a marked vasodilator (Tanaka et al, 1989;Suzuki et al, 1998). While there are no clinical studies evaluating the effects of cilostazol in hypercoagulable dogs and cats, the drug demonstrates potential as an effective anti-platelet therapy when used in models of human disease (Kimura et al, 1985;Tanaka et al, 1989;Saitoh et al, 1993). Other PDE3 inhibitors, such as milrinone, are primarily used in patients with congestive heart failure (Keister et al, 1990).…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…, an antiplatelet agent which acts as an inhibitor of cyclic AMP phosphodiesterase and thereby increases the cAMP concentration in platelets [11], or aspirin were added to PRP from normal subjects with heparin-induced small aggregate formation. Inhibition of heparin-induced small aggregates by each drug was measured as the difference between the light intensity before and after addition of the drug.…”
Section: Methodsmentioning
confidence: 99%